CrBPF1 overexpression alters transcript levels of terpenoid indole alkaloid biosynthetic and regulatory genes - Li, Chun Yao; Leopold, Alex L.; Sander, Guy W.; Shanks, Jacqueline V.; Zhao, Le; Gibson, Susan I. (Frontiers in Plant Science, 2015)
Terpenoid indole alkaloid (TIA) biosynthesis in Catharanthus roseus is a complex and highly regulated process. Understanding the biochemistry and regulation of the TIA pathway is of particular interest as it may allow the engineering of plants to accumulate higher levels of pharmaceutically important alkaloids. Towards this end, we generated a transgenic C. roseus hairy root line that overexpresses the CrBPF1 transcriptional activator under the control of a β-estradiol inducible promoter. CrBPF1 is a MYB-like protein that was previously postulated to help regulate the expression of the TIA biosynthetic gene STR. However, the role of CrBPF1 in regulation of the TIA and related pathways had not been previously characterized. In this study, transcriptional profiling revealed that overexpression of CrBPF1 results in increased transcript levels for genes from both the indole and terpenoid biosynthetic pathways that provide precursors for TIA biosynthesis, as well as for genes in the TIA biosynthetic pathway. In addition, overexpression of CrBPF1 causes increases in the transcript levels for 11 out of 13 genes postulated to act as transcriptional regulators of genes from the TIA and TIA feeder pathways. Interestingly, overexpression of CrBPF1 causes increased transcript levels for both TIA transcriptional activators and repressors. Despite the fact that CrBPF1 overexpression affects transcript levels of a large percentage of TIA biosynthetic and regulatory genes, CrBPF1 overexpression has only very modest effects on the levels of the TIA metabolites analyzed. This finding may be due, at least in part, to the up-regulation of both transcriptional activators and repressors in response to CrBPF1 overexpression, suggesting that CrBPF1 may serve as a “fine-tune” regulator for TIA biosynthesis, acting to help regulate the timing and amplitude of TIA gene expression.